Waminoa brickneri n. sp. (Acoela: Acoelomorpha) associated with corals in the Red Sea - Ogunlana, Maxina V.; Hooge, Matthew D.; Tekle, Yonas I.; Benayahu, Yehuda; Barneah, Orit; Tyler, Seth (Zootaxa, 2005)
While the majority of acoels live in marine sediments, some, usually identified as Waminoa sp., have been found associated with corals, living closely appressed to their external surfaces. We describe a new species collected from the stony coral Plesiastrea laxa in the Red Sea. Waminoa brickneri n. sp. can infest corals in high numbers, often forming clusters in non-overlapping arrays. It is bronze-colored, owing to the presence of two types of dinoflagellate endosymbionts, and speckled white with small scattered pigment spots. Its body is disc-shaped, highly flattened and circular in profile except for a small notch at the posterior margin where the reproductive organs lie. The male copulatory organ is poorly differentiated, but comprises a seminal vesicle weakly walled by concentrically layered muscles, and a small penis papilla with serous glands at its juncture with the male pore. The female system comprises a separate female pore, ciliated vagina, seminal bursa, 4–8 weakly sclerotized nozzles, and paired ovaries. Similarities with Haplodiscus spp. as well as features characteristic of the Convolutidae, including similarity in 18S rDNA sequence, warrant reassigning Waminoa to the Convolutidae.